Teacher training and autonomous learning in students of semester 2022-II (LACCEI, 2024)
The study made it possible to measure the degree of relationship between the variable Teacher Training and Autonomous Learning in university students. Methodologically, the quantitative approach was followed, with a non-experimental, correlational design, using the survey technique and the questionnaire as instruments. The population consisted of students of the National University of Trujillo in semester 2022-II. The results conclude that: (1) There is a significant relationship (p=0.0000290.01) in the variables studied, likewise the value of the correlation coefficient presented a positive sign, there is a direct relationship, whose strength of association is moderate positive. (2) The results show that 69.4 % of the students surveyed perceive the training of their teachers at the level of outstanding achievement, while 30.6 % perceive it as achieved. 36.1 % show an achieved level of autonomous learning, while 52.8 % are at the achieved level0 and only 11.1 % at the process level. (3) There is a significant relationship (p0.01) between the dimensions of the variable Teacher training and the variable Autonomous learning, in addition the relationships presented positive sign in each pair of correlations, which shows that these relationships are direct.